SEMANTIC INTERPRETATION OF CAUSATIVITY IN LINGUISTICS - Sanjarbek Abdulhamidov Xusnitdin o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of the article is to illustrate causative verbs in two languages, Uzbek and English as well as their features in the sentences. Moreover, it discusses semantic interpretation of causativity.